Effects of bone drilling on local temperature and bone regeneration: an in vivo study - Karaca, Faruk; Aksakal, Bunyamin; Kom, Mustafa (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2014)
Objective: The aim of this study was to examine the influence of bone drilling on local bone temperature and bone regeneration and determine optimal drilling speed and pressure in an animal model. Methods: The study included 12 skeletally mature New Zealand white rabbits, weighing between 2.8 to 3.2 kg. Rabbits were divided into 2 groups and euthanized at the end of Day 21 (Group A) and Day 42 (Group B). The same drilling protocol was used in both groups. Three drill holes with different pressure (5, 10 and 20 N) were made in each rabbit tibias using 3 different rotational drill speeds (230, 370 and 570 rpm). During drilling, local temperature was recorded. Rabbit tibia underwent histopathological exam for bone regeneration. Results: Bone temperature was affected by drilling time and depth. Lower drill speeds reduced the bone temperature and revealed better bone regeneration when compared to the drilled bones at higher drill speeds. Titanium boron nitride coating on the drill bits had no significant effects on bone temperature and structure. Bone regeneration was superior in Group B rabbits that had drilling at 230 rpm and 20 N. Conclusion: Our results suggested that lower drilling speed with higher pressure is necessary for better bone regeneration. The optimal drilling speed is 230 rpm and optimal drilling pressure 20 N.
Keywords: Bone healing; bone regeneration; drilling; histopathology; PARAMETERS; Orthopedics